Development of a functionalized UV-emitting nanocomposite for the treatment of cancer using indirect photodynamic therapy - Prakhar Sengar; Patricia Juárez; Andrea Verdugo-Meza; Danna L. Arellano; Akhil Jain; Kanchan Chauhan; Gustavo A. Hirata; Pierrick G. J. Fournier (Journal of Nanobiotechnology, 2018)
Abstract Background Photodynamic therapy is a promising cancer therapy modality but its application for deep-seated tumor is mainly hindered by the shallow penetration of visible light. X-ray-mediated photodynamic therapy (PDT) has gained a major attention owing to the limitless penetration of X-rays. However, substantial outcomes have still not been achieved due to the low luminescence efficiency of scintillating nanoparticles and weak energy transfer to the photosensitizer. The present work describes the development of Y2.99Pr0.01Al5O12-based (YP) mesoporous silica coated nanoparticles, multifunctionalized with protoporphyrin IX (PpIX) and folic acid (YPMS@PpIX@FA) for potential application in targeted deep PDT. Results A YP nanophosphor core was synthesized using the sol–gel method to be used as X-ray energy transducer and was then covered with a mesoporous silica layer. The luminescence analysis indicated a good spectral overlap between the PpIX and nanoscintillator at the Soret as well as Q-band region. The comparison of the emission spectra with or without PpIX showed signs of energy transfer, a prerequisite for deep PDT. In vitro studies showed the preferential uptake of the nanocomposite in cancer cells expressing the folate receptorFolr1, validating the targeting efficiency. Direct activation of conjugated PpIX with UVA in vitro induced ROS production causing breast and prostate cancer cell death indicating that the PpIX retained its activity after conjugation to the nanocomposite. The in vivo toxicity analysis showed the good biocompatibility and non-immunogenic response of YPMS@PpIX@FA. Conclusion Our results indicate that YPMS@PpIX@FA nanocomposites are promising candidates for X-ray-mediated PDT of deep-seated tumors. The design of these nanoparticles allows the functionalization with exchangeable targeting ligands thus offering versatility, in order to target various cancer cells, expressing different molecular targets on their surface.